Neurofilament light chain as a biomarker for acute hepatic porphyrias - Sgobbi, Paulo; Serrano, Paulo de Lima; Badia, Bruno de Mattos Lombardi; Farias, Igor Braga; Oliveira, Hélvia Bertoldo de; Barbosa, Alana Strucker; Pereira, Camila Alves; Moreira, Vanessa de Freitas; Pinto, Ícaro França Navarro; Oliveira, Acary Souza Bulle; Pinto, Wladimir Bocca Vieira de Rezende (Frontiers in Neurology, 2024)
Background Acute hepatic porphyrias (AHP) represent a rare group of inherited metabolic disorders of heme biosynthesis pathway. This study aims to determine the diagnostic and prognostic value of serum neurofilament light chain (NfL) as potential biomarker for AHP. Methods We conducted a cross-sectional observational study to evaluate NfL levels in patients with AHP. They were divided in different groups: normal health individuals; patients with definitive diagnosis of AHP during acute episodes; patients with AHP and infrequent attacks; patients with AHP and recurrent attacks; asymptomatic individuals with positive genetic testing and urinary delta-aminolevulinic acid (ALA) and porphobilinogen (PBG) levels elevated 4 or more times (“high excretors”); asymptomatic individuals with exclusive positive genetic test; control group with Hereditary Amyloidosis related to Transthyretin with Polyneuropathy (ATTRv-PN). Results During acute attacks, serum NfL levels were 68 times higher compared to normal controls and disclosed a strong correlation with ALA and PBG levels; also exhibited elevated levels in patients with chronic symptoms regardless of the number of disease attacks compared to healthy controls, and at similar levels to patients with ATTRv-PN, which is a model of progressive neuropathy. Conclusion This study represents the first to establish NfL as a biomarker for AHP, disclosing NfL as a sensitive biomarker for axonal damage and chronic symptom occurrence. This study not only underscores that neurological damage associated with the disease in any patient, irrespective of the number of attacks, but also reinforces the progressive and profoundly debilitating nature of acute and chronic symptoms observed in individuals with AHP.